Effects of preheating treatment on temperature distribution and material flow of aluminum alloy and steel friction stir welds. (October 2017) - Tang, Jingming; Shen, Yifu
Graphical abstract: Highlights: Friction stir welding (FSW) assisted by electric arc heating was used to join AA6061 aluminum alloy to E235A steel. The temperature distribution of the work-piece was investigated under the conditions of preheating and no preheating. The flow of the material was investigated under the conditions of preheating and no preheating. The temperature distribution of the work-piece was significantly changed by the preheating treatment. The flow velocity of the material improved significantly with preheating treatment. Abstract: Material flow and temperature distribution during welding are important factors that affect the properties of friction stir welding (FSW) joints. The scope of this investigation is to evaluate the effect of preheating treatment on the temperature distribution and material flow of aluminum alloy and steel joints produced by FSW. In this investigation, the finite volume model of butt FSW was established on basis of the FLUENT software. The flow of material during the FSW was simulated, and the temperature distribution in the FSW process was obtained by experiment and simulation. The effects of preheating treatment on the thermal history, temperature distribution, and material flow during FSW were elucidated in detail. The effects of preheating on the tensile strength and failure modes of the specimens were also discussed. The simulation shows that the preheating treatment increased the peak temperature of the steel, and also reduced the large temperature difference between the steel and the aluminum alloy in the high temperature stage. Simulation results, including temperature distribution and thermal history, were corresponded with the experimental results. The preheating treatment improved the flow velocities of the plastic materials and reduced the difference in flow velocities of the two materials. The preheating treatment could reduce the influence of the difference between the two materials on the forming of the welded joint and improve the property of the welded joint.